The development of educability motor-based warming model for long jump sports - Refiater, Ucok Hasian; Haryanto, Arief Ibnu (Jurnal Keolahragaan, 2024)
Stretching and warming up are crucial in every training session or competition in long jump athletics. This study was aimed at developing a warm-up model based on motor educability for the long jump sport. This research is a type of development with a research model procedure using Borg & Gall's five steps of the adaptation of the IOWA Brace Test to motor educability. The samples used in this research were media experts and material experts, each consisting of one person. For small group trials, there were 9 (nine) students from the Sports Science Study Program and for large group trials, there were 39 (thirty-nine) students from the Sports Coaching Education Study Program who took athletics courses. The instruments used were the 11 IOWA Brace Test motor educability items and the Standing Broad Jump test to examine effectiveness using the paired sample t test. As a result, in the expert validation step, revision, the design product has been declared feasible by the expert as well as during large and small group trials. The effectiveness test also revealed that there was a significant difference in the mean of paired samples. The results of this development also recommend several movements, namely: side learning rest, one knee balance, stroke stand, double heel kick, hop forward, forward hand kick, half squat-arm circle, side kick, russian dance, single squat balance, and jump foot. The conclusion is that of the eleven movements it is feasible to use in warm-up for the long jump sport. Future research needs to examine how this model supports athletes in improving physical fitness components.